The Influence of Flexible Working Arrangement on Job Satisfaction Mediated by Work-Life Balance Among Organic Employees - Putra, Anak Agung Gede Ngurah Pramana (Journal Of Social Science (JoSS), 2025)
This study investigates the impact of Flexible Working Arrangements (FWA) on Job Satisfaction, mediated by Work-Life Balance (WLB), among organic employees of PT Angkasa Pura Indonesia at I Gusti Ngurah Rai Airport, Bali. The research addresses concerns regarding job satisfaction in the context of shift work systems that are perceived as disorganized and disruptive to employees' personal lives. The objective is to examine whether FWA directly influences job satisfaction and indirectly through WLB. Utilizing a quantitative approach with an associative causal design, the study involved a saturated sampling of 128 employees. Data were collected through structured questionnaires and interviews and analyzed using path analysis via SPSS, including regression tests, normality, multicollinearity, heteroscedasticity, and Sobel test. The findings indicate that FWA has a significant positive effect on both WLB and job satisfaction, and that WLB significantly mediates the relationship between FWA and job satisfaction. These results support the social exchange theory, suggesting that employees respond positively to organizational flexibility by enhancing their commitment and satisfaction. The practical implication highlights the need for companies to evaluate and implement flexible scheduling policies to improve employee well-being and performance. Theoretical implications reinforce the role of WLB as a crucial mediator in organizational behavior studies. Future research could explore comparative models across different industries or regions.